Restoration of endodontically treated mandibular molar tooth with semi-indirect bonded restoration using single shade composite resin: A case report - Juwita, Ratna; Dwiandhany, Wahyuni S.; Nugroho, Juni J.; Hikmah, Noor; Natsir, Nurhayaty; Trilaksana, Aries C. (Journal of Case Reports in Dental Medicine, 2023)
Objective: This case report aimed to describe the restoration of endodontically treated mandibular molar tooth with semi-indirect bonded restoration using single shade composite resin.Methods: Endodontic treatment for tooth #36 with asymptomatic irreversible pulpitis. After root canal obturation, treatment was continued with semi-indirect bonded restoration using single shade composite resin. An impression was taken using alginate and then poured with silicone material (Silicone Die, Voco) to produce the model. Single shade composite resin (Omnichroma, Tokoyama Dental) was used to build up the restoration layer by layer in 2 mm increments up to the occlusal surface.Results: After 1 month of control, objective and subjective examinations were carried out on the patient, there were no complaints, indicating the tooth is functioning well and the patient is satisfied with the restorationConclusion: Restoration of endodontically treated mandibular molar tooth with semi-indirect bonded restoration using single shade composite resin in this case gives satisfactory results to restore function and esthetics